Studi Komparasi Pemikiran Ekonomi Islam Syed Nawab Haider Naqvi dengan Yusuf Al-Qardhawi - Muhammad Irwin Muslimin; Darwanto Darwanto (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The existence of Islamic Economics in recent years has risen. This makes the development of Islamic Economics more diverse. This needs to be addressed wisely by examining various points of views, including the thoughts of Islamic Economists regarding the Islamic Economic System, so that the knowledge about the Islamic Economic System is fundamentally known by various parties. This research uses a qualitative method using library research method with a comparative approach. This literature research explains and compares the thoughts of two contemporary Islamic Economists, namely Syed Nawab Haider Naqvi and Yusuf Al-Qardhawi. The data analysis technique used is content analysis and comparison. Union intersection tool is used to compare several dimensions of the thoughts of the two Islamic Economists regarding Islamic Economic System. The results of the research show that the thoughts of Syed Nawab Haider Naqvi and Yusuf Al-Qardhawi regarding Islamic Economic System are related to each other and classified into the same dimensions of basic views, economic ethics and government roles. Syed Nawab Haider Naqvi is famous for his approach of axiomatic approach and Yusuf Al-Qardhawi through ethical approach. Both support integrating Islamic norms and ethics that are sourced from the Qur'an and Hadith into every economic activity.